Coordenação de curso no ensino superior: atuação, funções, possibilidades e limites - Justo, Maria Christina (2014)
The purpose of this research is to investigate the possibilities and limitations of action that a Course Coordinator has in his work as an educational manager of a University Center. The methodology applied herein was a qualitative approach with features of a case study. The research was developed through literature review, documental analysis and field research. Data were collected through observation, questionnaires and a focus group. Its setting was a Higher Education Institution in the state of São Paulo. These data, having as subject course coordinators, were analyzed and included in this study. As a result of the research, it was possible to recognize the dimensions of the performance and to characterize the roles of course coordinators in University Centers, and to clarify the actions that are relevant to their performance in the organization and operation of their courses. Moreover, there is evidence that, despite the work load of a course coordinator, the outcomes of formative and developmental proposals for higher education teachers may benefit from the intervention of this professional. This research does not intend to be exhaustive, but rather to foster studies related to the challenges and demands regarding the work of course coordinators in private higher education institutions, including the continuing education of teachers under their responsibility. Further investigations may be developed from the contributions presented in this work, expanding the meaning of this professional within higher education